Transcriptome analysis provides insights into the mechanism of carapace stripe formation in two closely related Marsupenaeus species - Wang, Panpan; Xie, Shumin; Li, Xinyang; Zhu, Jiawei; You, Ziqi; Zhou, Xinlei; Zhou, Xinyi; Yan, Binlun; Gao, Huan; Xing, Chaofan (Frontiers in Marine Science, 2023)
Marsupenaeus japonicus has two types of phenotypic differences that are mainly reflected in the stripe pattern of the carapace. However, the underlying mechanism regulating the stripe patterns is not clear. In the present study, we first observed the composition of pigment cells and detected the contents of different carotenoids in the carapace of M. japonicus. We clearly observed the setae structure on the carapace. There were red pigment cells in the stripe pattern and yellow pigment cells in the other parts. Both red pigment cells and yellow pigment cells showed dendritic morphology. In the carapace, the content of astaxanthin was the highest, significantly (P < 0.05) higher than that of other carotenoids. Some differentially expressed genes between two pattern types of M. japonicus, may be associated with the body color formation, such as crustacyanin (CRCN), apolipoprotein D (ApoD), tubulin alpha-1 chain, cuticle protein, and ABC transporter, which were verified by quantitative PCR experiments. The amino acid composition and secondary structure of CRCN A2, CRCN C1, and ApoD were significantly different. The results of this study will help to elucidate the molecular mechanism of the differential pattern formation of M. japonicus and provide a reference for further exploration of the formation mechanism of crustacean color.